Magnetostatic Modelling of Thin Layers Using the Method of Moments And Its Implementation in OCTAVE/MATLAB - Szewczyk, Roman (Lecture Notes in Electrical Engineering,, 2018)
This book presents an efficient and robust method of modelling the magnetostatic properties of different technical elements, especially thin layers for magnetic sensors. The solutions presented utilise the principles of the method of moments. However, the principles have been developed both from the point of view of physical analyses as well as from the point of view of numerical optimisation. To enable cost-efficient use of the solutions for commercial applications in industry, the proposed method was implemented as a code optimised for use in the open-source OCTAVE environment. The scripts can be also used with MATLAB software, which is more user friendly, especially for less experienced users.